Linking loss aversion and present bias with overspending behavior of tourists: Insights from a lab-in-the-field experiment. (June 2016) - Nguyen, Quang
Abstract: Building upon Prospect Theory and Hyperbolic Time Discounting models, we explore how behavioral factors influence the probability of overspending among outbound leisure travelers. We construct our data in two steps. First, we collect demographics and travel-related variables from a random sample of 314 Singaporean tourists across different age groups and income levels. Second, we conduct a field experiment to measure their risk and time preferences, specifically loss aversion and present bias. We then explore the link between the measured preferences to overspending behavior. The findings reveal an interesting link between loss aversion, present bias and traveling expenditure patterns: outbound tourists with high loss aversion and high present bias are more likely to overspend. Finally, our study also highlights the role of group identity in de-biasing. Specifically, individuals are more likely to behave according to standard economic models when making decisions in groups. Highlights: We integrate Prospect Theory and hyperbolic discounting into a single framework. We explore the role of loss aversion and present bias in the tourist's overspending behavior. The analysis is based upon a unique data set that combines economic experiments and a survey. The findings reveal interesting roles of loss aversion and present bias in tourists' behavior. Tourists with high loss aversion and high present bias are more likely to overspend. Finally, our study also highlights the role of group identity in de-biasing. Individuals are more likely to behave rationally when making decisions in groups.